Strategic Management in Strengthening Religious Moderation: A Case Study in Primary Schools - Aruman, Iman; Hasbi, Hasbi; Firman, Firman; Ilham, Dodi (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palopo), 2024)
Indonesia’s rich cultural and religious diversity presents both opportunities and challenges, particularly in fostering social harmony in pluralistic societies. This study examines the management of religious moderation in two primary education institutions, Madrasah Ibtidaiyah Swasta (MIS) Rantepao and SD Katolik Rantepao III, located in North Toraja Regency. Using a descriptive qualitative research design, the study explores the implementation, strategic steps, and challenges of strengthening religious moderation within these schools. Findings reveal that religious moderation is tailored to the unique contexts of each institution. MIS Rantepao integrates Islamic values with community engagement through activities such as celebrating Islamic holidays and promoting social harmony among students. Conversely, SD Katolik Rantepao III emphasizes humanistic values, inclusivity, and interfaith respect, creating a learning environment that prioritizes egalitarianism and collaboration. Both schools also incorporate nationalism and civic education, reinforcing unity through Indonesia’s foundational principles of Pancasila. Systematic steps, such as lesson planning, diverse teaching methodologies, and inclusive character education, demonstrate the commitment of both schools to fostering tolerance and inclusivity. Despite their efforts, challenges persist, including resource limitations, internal religious differences, and navigating local cultural traditions. These challenges underscore the need for sustained dialogue, enhanced resources, and innovative strategies to support religious moderation. This study contributes to understanding the role of education in promoting tolerance and social cohesion in multicultural societies. The findings offer practical insights for educators and policymakers aiming to foster inclusivity and harmonious coexistence through educational institutions.